Beneficial effect of butyrate‐producing Lachnospiraceae on stress‐induced visceral hypersensitivity in rats - Zhang, Jindong; Song, Lijin; Wang, Yujing; Liu, Chang; Zhang, Lu; Zhu, Shiwei; Liu, Shuangjiang; Duan, Liping (Journal of gastroenterology and hepatology, 2019)
Background and Aim Emerging evidence indicates that psychological stress is involved in the pathogenesis of irritable bowel syndrome, which is characterized by visceral hypersensitivity and may be accompanied by gut dysbiosis. However, how such stress contributes to the development of visceral hypersensitivity is incompletely understood. Here, we aimed to investigate the influence that stress‐induced microbial changes exert on visceral sensitivity, as well as the possible underlying mechanisms associated with this effect. Methods Male Sprague–Dawley rats underwent chronic water avoidance stress (WAS) to induce visceral hypersensitivity. Visceral sensitivity, colonic tight junction protein expression, and short‐chain fatty acids of cecal contents were measured. Fecal samples were collected to characterize microbiota profiles. In a separate study, oral gavage of Roseburia in WAS rats was conducted to verify its potential role in the effectiveness on visceral hypersensitivity. Results Repeated WAS caused visceral hypersensitivity, altered fecal microbiota composition and function, and decreased occludin expression in the colon. Stressed rats exhibited reduced representation of pathways involved in the metabolism of butyrate and reduced abundance of several operational taxonomic units associated with butyrate‐producing bacteria, such as Lachnospiraceae. Consistently, supplementation with Roseburia hominis, a species belonging to Lachnospiraceae, significantly increased cecal butyrate content. Moreover, Roseburia supplementation alleviated visceral hypersensitivity and prevented the decreased expression of occludin. Conclusions Reduction in the abundance of butyrate‐producing Lachnospiraceae, which is beneficial for the intestinal barrier, was involved in the formation of visceral hypersensitivity. R. hominis is a potential probiotic for treating stress‐induced visceral hypersensitivity.